Cultural memory in Deuteronomy 4 and 32 - Yu, Jihye (Journal for the study of the Old Testament, 2026)
Deuteronomy repeatedly calls Israel to remember its foundational narratives and warns against forgetting, employing various strategies throughout the book to aid cultural memory. Such memory involves the continual reinterpretation and reconstruction of the past to align with contemporary situations, needs, and perspectives, thereby guiding the audience in projecting the future. This article analyzes Deuteronomy 4 and 32, demonstrating how cultural memories are intentionally constructed through specific mnemonic techniques to serve as a foundational framework for these chapters. It argues that narratives of YHWH?s enduring love and special treatment of Israel are strategically shaped in response to the audience?s present needs, causing remembered pasts and projected futures to converge, defining Israel?s covenantal identity and obligations. The article contends that these constructed memories guide Israel toward covenantal loyalty and obedience to the Law, presenting monolatry as both a product of past memory and a prescriptive cultural memory for the future. Ultimately, Deuteronomy?s sophisticated use of memory work, including YHWH?s active participation within that memory, serves a persuasive and community-forming agenda rooted in Israel?s unique relationship with him.